Benefits and challenges of reviewing across knowledge systems: ‘Gourmet omnivore’ pigs foraging in the wild - Zsolt Molnár; László Demeter; Klára Szabados; Alen Kiš; Milutin Ajvazović; Borislav Runjanin; Vlada Mandušić; Marianna Biró; Kinga Öllerer; Jelena Marinkov; Viktor Ulicsni; Dániel Babai; et al. (People and Nature)
Abstract Evidence‐based conservation can benefit substantially from multiple knowledge sources and different knowledge systems. While traditional ecological knowledge (TEK) and collaborative research are increasingly acknowledged, detailed cross‐knowledge system reviews are scarce and their methodology underdeveloped. We have two objectives: to prepare such a review and to discuss the benefits and challenges of such reviews. We review pig keeping in forests and marshes, a historically widespread but nowadays almost extinct practice in Europe, but one with high potential for organic farming, conservation and restoration. We focus on what, when and how free‐ranging pigs forage in the wild. We review five knowledge sources: living and archived TEK, pig and wild boar scientific literature, and the authors' observations of foraging. Unexpectedly, given the amount of available information, archived TEK differed considerably from living TEK of svinjars (Serbian: traditional pig keepers), and scientific knowledge on pig and boar foraging from TEK. Svinjars deeply understood the consumption and avoidance behaviour of pigs towards 98 and 56 plant taxa, and 42 and 17 animal taxa, respectively. Our review showed that pigs are gourmet omnivores, optimizing and switching between foraging on earthworms, acorns, grasses and corn. Discrepancies between knowledge sources were rare, for example on the consumption of woody roots, earthworms, mushrooms and snakes/lizards. Sources were also complementary, filling each other's knowledge gaps. Topics where the cross‐knowledge system review was most fruitful were acorn foraging, browsing, earthworm and mushroom consumption. Differences in the contributions of the knowledge sources to the enriched picture resulted from the diverging interests and methodologies of the knowledge generators. We identified and discussed both the benefits (different approaches of knowledge generation; expanded time scales; complementarity; novel cause–effect explanations; identification of knowledge gaps; and biases) and the challenges (how to identify relevant publications and knowledgeable TEK holders; how to collate knowledge and verify its reliability; and how to conduct a culturally respectful synthesis) of cross‐knowledge system reviewing. Synthesis and applications. Cross‐knowledge system reviews help overcome limitations in ecological understanding and may provide a shared understanding among collaborating partners, build trust and foster acceptance of each other's knowledge as legitimate. Read the free Plain Language Summary for this article on the Journal blog.